Thyroid Disease as a Professional Hazard - Soni, Abhishek; Singh, Sunder; Verma , Monica; Chauhan, Ashok; Kaushal, Vivek (Emerging Trends in Disease and Health Research Vol. 8, 2022)
The thyroid gland produces thyroid hormones which controls metabolism of the body and it is at risk of radiation exposure among health care workers in the field of radiation oncology, radiology, cardiology, neurology, physicians and other paramedical staff. Radiation induced different thyroid diseases include hypothyroidism, thyroiditis and auto-immune thyroid disease. Cancer has not been associated with the occupational exposure even in long follow up studies. Radiation induced thyroid disease is an emerging professional hazard especially in the developed countries attributing to health care infrastructure. This hazard may be prevented by using thyroid shield. There are some organizations controlling the occupational limits of radiation exposure among health care workers and that is strictly monitored. Research is going on thyroid peroxidase to establish as marker for radiation induced thyroid damage. As thyroid gland is involved in body homeostasis, more studies should be done by recruiting greater number of health care workers so as to develop guidelines to prevent thyroid exposure and to formulate management guidelines based on the early stage markers.